Rezolvati in Z ecuatia: (x-1)/2 - (x-2)/3 = 0
Răspunsuri la întrebare
Răspuns de
1
(x-1)/2-(x-2)/3=0
=>![\frac{3x-3}{6} - \frac{2x-4}{6} = \frac{x+1}{6} = 0 \frac{3x-3}{6} - \frac{2x-4}{6} = \frac{x+1}{6} = 0](https://tex.z-dn.net/?f=+%5Cfrac%7B3x-3%7D%7B6%7D+-+%5Cfrac%7B2x-4%7D%7B6%7D+%3D++%5Cfrac%7Bx%2B1%7D%7B6%7D+%3D+0+)
(x+1)/6=0 => x+1=0 => x=-1
=>
(x+1)/6=0 => x+1=0 => x=-1
Răspuns de
0
(x-1)/2-(x-2)/3=0
=>
(x+1)/6=0 => x+1=0 => x=-1 ...
=>
(x+1)/6=0 => x+1=0 => x=-1 ...
Alte întrebări interesante
Engleza,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Istorie,
9 ani în urmă
Matematică,
9 ani în urmă